Managing pediatric otorhinolaryngology patients in coronavirus disease-19 pandemic – A real challenge to the clinicians - Swain, Santosh Kumar; Behera, Ishwar Chandra (Indian Journal of Child Health, 2020)
The novel coronavirus disease (COVID-19) pandemic is posing unprecedented challenges among the otolaryngologists during managing the pediatric patients. COVID-19 infection is caused by novel coronavirus called severe acute respiratory syndrome coronavirus-2. This infection is transmitted primarily through human contact and by droplet route. The pediatric otolaryngologists have a critical role for managing nose, paranasal sinus, ears, oral cavity, pharynx, and larynx, which are important sites for generating aerosols and virus transmission. Asymptomatic pediatric patients have high risk for viral shedding. In COVID-19 pandemic, the surgical procedure by pediatric otolaryngologists should be limited to the emergency condition. The surgical interventions should limit the viral dissemination. This review article provides an overview of common methods to limit the viral transmission to the otolaryngologists and assisting health-care staffs from COVID-19 infections during the management of the pediatric patients.